Complementation analysis of Agrobacterium tumefaciens Ti plasmid mutations affecting oncogenicity. - Klee, H J (1982)
A wide host range cosmid vector has been constructed by insertion of the lambda cos site into the plasmid pRK2501. This cosmid, which is maintained in Agrobacterium tumefaciens and is compatible with the Ti plasmid, has been used to make a clone bank of the A. tumefaciens pTiA6 plasmid. Several pTiA6 cosmids have been used to complement Tn5-induced Ti plasmid mutations. Five avirulent mutations which map outside of the region of the plasmid maintained in plant tumours (T-DNA) could be complemented in a trans orientation. Two mutations which are located on a single HpaI restriction fragment outside of the T-DNA, as well as three mutations which map within the T-DNA region, could not be complemented in a trans orientation in a REC- host.